The infective causes of hepatitis and jaundice amongst hospitalised patients in Vientiane, Laos. - Syhavong, B; Rasachack, B; Smythe, L; Rolain, J; Roque-Afonso, A; Jenjaroen, K; Soukkhaserm, V; Phongmany, S; Phetsouvanh, R; Soukkhaserm, S; Thammavong, T; Mayxay, M; et al. (2010)
There is little information on the diverse infectious causes of jaundice and hepatitis in the Asiatic tropics. Serology (hepatitis A, B, C and E, leptospirosis, dengue, rickettsia), antigen tests (dengue), PCR assays (hepatitis A, C and E) and blood cultures (septicaemia) were performed on samples from 392 patients admitted with jaundice or raised transaminases (> or =x3) to Mahosot Hospital, Vientiane, Laos over 3 years. Conservative definitions suggested diagnoses of dengue (8.4%), rickettsioses (7.3%), leptospirosis (6.8%), hepatitis B (4.9%), hepatitis C (4.9%), community-acquired septicaemia (3.3%) and hepatitis E (1.6%). Although anti-hepatitis A virus (HAV) IgM antibody results suggested that 35.8% of patients had acute HAV infections, anti-HAV IgG antibody avidity and HAV PCR suggested that 82% had polyclonal activation and not acute HAV infections. Scrub typhus, murine typhus or leptospirosis were present in 12.8% of patients and were associated with meningism and relatively low AST and ALT elevation. These patients would be expected to respond to empirical doxycycline therapy which, in the absence of virological diagnosis and treatment, may be an appropriate cost-effective intervention in Lao patients with jaundice/hepatitis.